Modeling Consumers' Adoption Intentions of Remote Mobile Payments in the United Kingdom: Extending UTAUT with Innovativeness, Risk, and Trust. Issue 8 (August 2015) - Slade, Emma L.; Dwivedi, Yogesh K.; Piercy, Niall C.; Williams, Michael D.
ABSTRACT Mobile payments (MPs) are predicted to be one of the future's most successful mobile services but have achieved limited acceptance in developed countries to date. PCs are still the preferred technology for online shopping in the United Kingdom but the continued growth of mobile commerce (MC) is highly correlated with the success of remote MPs (RMPs). Currently MP research has largely ignored the variations between different MP solutions, and existing MP adoption studies have predominantly utilized Davis' (1989) Technology Acceptance Model, which has been criticized for having a deterministic approach without much consideration for users' individual characteristics. Therefore, this study applied the Unified Theory of Acceptance and Use of Technology (UTAUT), extended with more consumer‐related constructs, to explore the factors affecting nonusers' intentions to adopt RMP in the United Kingdom. Quantitative data were collected (n = 268) and structural equation modeling was undertaken. The findings revealed that performance expectancy, social influence, innovativeness, and perceived risk significantly influenced nonusers' intentions to adopt RMP, whereas effort expectancy did not. Inclusion of MP knowledge as a moderating variable revealed that there was a significant difference in the effect of trust on behavioral intention for those who knew about MP than for those who did not. These findings have important theoretical and practical implications, particularly for the development and marketing of RMP, which will support the long‐term success of MC.